Relationship between dental loss and health outcomes among hospitalized patients with and without diabetes. (March 2019) - Izuora, Kenneth; Yousif, Ammar; Allenback, Gayle; Gewelber, Civon; Neubauer, Michael
There is mixed evidence regarding the impact of poor dental health on cardiovascular disease and other health outcomes. Our objective was to determine the outcomes associated with poor dental health among hospitalized patients with and without diabetes mellitus (DM) at our institution. We enrolled a consecutive sample of adult patients admitted to an academic medical center. We gathered demographic, health and dental information, reviewed their medical records and then examined their teeth. We analyzed data using SPSS V.24. There was a high prevalence of dental loss among all hospitalized patients. Older age (p<0.001), smoking (p=0.034), having DM (p=0.001) and lower frequency of teeth brushing (p<0.001) were predictors of having a lower number of healthy teeth. Among DM and non-DM patients, fewer remaining healthy teeth was associated with presence of heart disease (p=0.025 and 0.003, respectively). Patients with diabetes mellitus (DM) had a higher prevalence of stroke (p=0.006) while patients without DM had a higher number of discharge medications (p=0.001) associated with having fewer number of healthy teeth. There was no correlation between number of healthy teeth and the length or frequency of hospitalization. Patients with DM are more likely to have fewer number of healthy teeth compared with non-DM patients. Fewer number of healthy teeth was associated with higher prevalence of heart disease in both DM and non-DM patients and with more discharge medications in non-DM patients.